If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + x + 8 = -3x + -2 Reorder the terms: 8 + X + x = -3x + -2 Reorder the terms: 8 + X + x = -2 + -3x Solving 8 + X + x = -2 + -3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + X + -8 + x = -2 + -8 + -3x Reorder the terms: 8 + -8 + X + x = -2 + -8 + -3x Combine like terms: 8 + -8 = 0 0 + X + x = -2 + -8 + -3x X + x = -2 + -8 + -3x Combine like terms: -2 + -8 = -10 X + x = -10 + -3x Add '-1x' to each side of the equation. X + x + -1x = -10 + -3x + -1x Combine like terms: x + -1x = 0 X + 0 = -10 + -3x + -1x X = -10 + -3x + -1x Combine like terms: -3x + -1x = -4x X = -10 + -4x Simplifying X = -10 + -4x
| 2.25(2x+.75)= | | 2y=6/x | | 21-8(v+3)+3+7v=p | | 0.75a-9= | | x-1=3/4x+1 | | 6x+4=-7+7x | | 1/3x4/3 | | 4x+(-4x+5)=12 | | (x+1)(x-3)(x^2-6x+18)=equation | | 0.30=log(1/x) | | 1/3x4/3= | | ln(7k-3)=2 | | 0.30=log(1/T) | | 0.25(d+56)=55 | | -8x-3(-4x-6)=10 | | (4+3n)+(5+4d)= | | -8-b+4b-2-3b= | | -8-3p=8(1+8p) | | (x+1)(x-3)(x-6x+18)=equation | | 2x+10=90-(4x+20) | | (-4,11);m=3/4 | | 768=4(x+18) | | 0.25(d+56)=64 | | 2x^2+7=12 | | 3x^4+18=21x | | 7x+-13=6x+-17 | | 15-3k=10(k-5) | | (2m)3/5 | | 90=33 | | 6(r-4)+r+30-7r=p | | 1,134=6(x+16) | | 1x+4x+6x= |